GREEN FINANCE DALAM MENDUKUNG SUSTAINABLE DEVELOPMENT: STUDI SYSTEMATIC LITERATURE REVIEW 2019-2025 - Abhull Azwad, Nugraha; Syam, Nurkumalasari (Gapenas Publisher, 2025)
environment, which in the last decade has increasingly relied on the Green Finance mechanism. However, the current literature shows that there is an imbalance in the focus of research, especially the lack of studies that link the role of green finance to the three pillars of development comprehensively. This study aims to map the development of research on the implementation of green finance in supporting sustainable development by conducting a Systematic Literature Review (SLR) of 76 Scopus indexed articles in the 2019–2025 period. The PRISMA method is used for the process of identifying, filtering, and selecting articles, which are then analyzed using content analysis instruments based on six main aspects: year of publication, country, journal classification, journal tier, research design, and category of green finance implementation of economic, environmental, and social pillars. The results show that the trend of publications continues to increase with the dominance of quantitative studies and quality journals in Q1. China is the most dominant research context, followed by global studies and developing countries. In terms of implementation, the most research attention was focused on the economic (50%) and environmental (47.2%) pillars, while the social aspect only received a portion of 2.8%. Green finance instruments such as green credit, green bonds, financial digitalization, and technological innovation have been proven to encourage clean energy investment, resource efficiency, and sustainable economic growth. However, the social dimension is still less integrated, although several studies show contributions through green human resource management, sustainability literacy, and improving community welfare. These findings open up new research space related to the integration of green finance with social welfare, inclusivity, and sustainable justice, as well as the importance of regulatory harmonization and the provision of credible environmental data to strengthen its implementation in various countries